Faktor-Faktor Yang Berhubungan Dengan Efektifitas Pelayanan Kesehatan Berbasis Gugus Pulau Di Puskesmas Pasanea Kecamatan Seram Utara Barat Kabupaten Maluku Tengah Tahun 2019 - Maritje Seflin J. Malisngorar (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
The health sector as one of the sectors that supports the success of accelerated development has sought to increase access to quality health services efficiently and effectively through the strategy of island groups in the health sector to realize an increase in health status.The concept of island groups in the health sector in Maluku Province is inseparable from the policy of the Maluku provincial government in implementing island cluster-based development in order to accelerate the improvement of community welfare and equitable development between regions in the Maluku region as an archipelago by taking into account the infrastructure, human resources and management suggestions that the Research has This aims to determine the factors related to the effectiveness of island cluster-based health services at the Pasanea Health Center, Seram Utara Barat District in 2019. The type of research used is descriptive analytic research with a cross sectional approach with a total sample of 21 respondents. The results showed that of the three factors that the researchers took, namely, infrastructure, Human resources and management of the Puskesmas are known to have a close relationship with the effectiveness of health services at the Pasanea Puskesmas. The results of the Spearman Rho test showed that the relationship between facilities and infrastructure and the effectiveness of health services was p = 0.002, the relationship between human resources and the effectiveness of health services was p = 0.005 and management with the effectiveness of health services with a value of p = 0.005. From the results of this study, it can be concluded that there is a significant relationship between infrastructure, human resources and management with the effectiveness of health services at Pasanea Health Center, West Seram District in 2019. the relationship between human resources and the effectiveness of health services p = 0.005 and management with the effectiveness of health services with a value of p = 0.005. From the results of this study, it can be concluded that there is a significant relationship between infrastructure, human resources and management with the effectiveness of health services at Pasanea Health Center, West Seram District in 2019. the relationship between human resources and the effectiveness of health services p = 0.005 and management with the effectiveness of health services with a value of p = 0.005. From the results of this study, it can be concluded that there is a significant relationship between infrastructure, human resources and management with the effectiveness of health services at Pasanea Health Center, West Seram District in 2019. Keywords: infrastructure; human resources; management; service effectiveness; public health center ABSTRAK Sektor kesehatan sebagai salah satu sektor yang mendukung keberhasilan percepatan pembangunan telah berupaya meningkatkan akses pelayanan Kesehatan bermutu dengan efisien dan efektif melalui strategi gugus pulau dibidang Kesehatan untuk mewujudkan peningkatan status Kesehatan. Konsep gugus pulau bidang Kesehatan di Provinsi Maluku tidak lepas dari Kebijakan pemerintah daerah provinsi Maluku dalam menerapkan Pembangunan berbasis gugus pulau dalam rangka mempercepat peningkatan kesejahteraan masyarakat dan pemerataan pembangunan antar wilayah di daerah Maluku sebagai wilayah kepulauan dengan memperhatikan saran prasarana, SDM dan manejemn yang dimiliki Penelitian ini bertujuan untuk mengetahui, faktor-faktor yang berhubungan dengan efektifitas pelayanan kesehatan berbasis gugus pulau di Puskesmas Pasanea Kecamatan Seram Utara Barat tahun 2019. Jenis penelitian yang di gunakan adalah penelitian deskriptif analitik dengan pendekatan cross sectional dengan jumlah sampel sebanyak 21 responden. Hasil penelitian menunjukkan bahwa dari tiga faktor yang peneliti ambil yakni, sarana prasarana, SDM dan Manajemen Puskesmas diketahui bahwa ketiganya memiliki hubungan yang erat dengan efektivitas pelayanan kesehatan di Puskesmas Pasanea. Hasil uji Spearman Rho diperoleh niali hubungan sarana prasarana dengan efektivitas pelyanan kesehatan yakni p= 0,002, hubungan SDM dengan efektivitas pelyanan kesehatan p= 0,005 dan manajemen dengan efektivitas pelyanan kesehatan dengan nilai p= 0,005. Dari hasil penelitian tersebut dapat disimpilkan bahwa ada hubungan yang signifikan antara srana prasarana, SDM dan manejemen dengan efektifitas pelayanan kesehatan di Puskesmas Pasanea Kecamatan Seram Utara Barat tahun 2019 Kata kunci: sarana prasarana; sumber daya manusia; manajemen; efektifitas pelayanan; puskesmas